PENINGKATAN PENGETAHUAN DAN EDUKASI PENCEGAHAN PERILAKU PROMISKUITAS PADA SISWA SMA - isnugroho, hernawan; Trisnaningsih, Rahma; Widya K, Raden Rama (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2023)
This activity discusses efforts to enhance knowledge and education regarding the prevention of promiscuous behavior among high school students. The activity provides insights into the implementation of prevention measures, identifying the effectiveness of an educational program in improving knowledge about preventing promiscuous behavior. The method employed is a lecture-based activity within an educational program. The outcomes of this activity are expected to offer guidance to schools and other educational institutions in designing similar educational programs, supporting the development of improved educational programs that have a positive impact on student behavior..